Interfacing with Power: Orders and Computers (Cinéma & Cie. Film and Media Studies Journal, 2017)
Any interest in the relationship between today’s popular culture and images or visibility cannot escape the sustained signi cance of images delivered by various forms of graphical user interfaces. Since these interfaces are not only tools or even mere preparations of presentations but meaningful presentations themselves, this essay proposes to analyze them as operative images. By delivering a sort of signs, that combine iconic as well as symbolic and indexical qualities, operative images sketch out and perform interrelated concepts of both: the user and the computer/the digital.From this follows the importance of analyzing popular interfaces as a special kind of staging – as a mise-en-scène ‘depresenting’ the power and work of the computer and interrelating with the promises/fears shaping the myth of ‘the digital’ since the late 1980s. Struggling for a critical position against the mythical term ‘digital’, I have proposed the neologism ‘digitalicity’ [Digitalizität]. I will argue that establishing the analysis of ‘interface-mise-en-scène’ as something like a vital part of today’s media studies is largely and indeed long overdue. The graphical user interface of YouTube will be taken here as a case study. It will be discussed as a particular performance of the ‘aesthetics of regulation’ [Ästhetik der Verfügung], that informs the aesthetical appearance of computers, allowing and framing our handling with them. Characterized by a dialectic motion, the aesthetics of regulation raises questions of power: interfaces empower users to regulate and condemn them to be regulated at the same time.